Heritage schools: A lens through which we may better understand citizenship and citizenship education. Issue 1 (1st March 2017) - Reed, Beatrice Szczepek; Said, Fatma; Davies, Ian
Heritage schools are part-time community-based educational institutions offering language and cultural education. In this article we recognize that the UK government is keen to promote diverse, enterprising, community-based educational action and, simultaneously, keen to promote a particular values-based national identity. In general terms, we would expect Heritage schools to be supported for their contribution to communities and as an example of enterprise, but they are instead viewed by the government with suspicion. Following introductory comments, the bulk of the article is given over to an identification of and discussion about seven tensions in debates about Heritage schools that illuminate thinking and practice about aspects of citizenship and citizenship education. Our argument is that by considering these tensions we can illuminate the nature of citizenship and character education. We address two fundamental and contextual tensions by looking at general issues of freedom and control in educational policy and the characterization of Heritage schools. We then discuss five other tensions to do with equality, diversity, achievement, language education and finally the teaching and learning of citizenship and character.